Alfredo Civita filosofo della mente (Materiali di Estetica. Terza serie, 2018)
This brief paper focuses on Alfredo Civita’s contribution to the philosophical reflection on the mind, with particular attention to his most meditated and coherent work, Saggio sul cervello e la mente (Guerini, 1993). From this book the ability to make three ingredients interact equally emerges as a characteristic of the still very current Civita’s thought: originality, methodological rigor and convergence between theoretical reflection and clinical practice.